Correction: A cross population between D. kaki and D. virginiana shows high variability for saline tolerance and improved salt stress tolerance. - Francisco Gil-Muñoz; Juan Gabriel Pérez-Pérez; Ana Quiñones; Amparo Primo-Capella; Jaime Cebolla; Mª Ángeles Forner-Giner; Maria L Badenes; Mª Del Mar Naval (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0229023.].